2012
DOI: 10.1159/000339993
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Substitutions in the Hepatitis C Virus Core Region and Lipid Metabolism Are Associated with Hepatocarcinogenesis in Nonresponders to Interferon plus Ribavirin Combination Therapy

Abstract: Background: Substitution of amino acid 70 and/or 91 in the core region of hepatitis C virus (HCV) genotype 1b (HCV-1b) is an important predictor of hepatocellular carcinoma (HCC), but its impact on HCC in nonresponders to interferon (IFN) and ribavirin (RIB) combination therapy is not clear. Methods: A total of 292 patients with HCV-1b-related chronic liver disease who did not achieve a sustained virological response to 24–48 weeks of IFN+RIB combination therapy were included in a follow-up study to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Although high-density lipoprotein (HDL), as a lipid metabolite, is known as “good cholesterol,” with the main function of reverse cholesterol transport (RCT) and negative correlation with atherosclerosis [8], little is known about alterations of metabolism, especially HDL, and how these multi-level variations affect aggressive diseases and poor outcomes. Patients with hepatitis B or hepatitis C have been shown to have possible lipid disorders, including decreased plasma HDL [5, 9]. However, whether HDL levels are correlated with HCC prognosis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although high-density lipoprotein (HDL), as a lipid metabolite, is known as “good cholesterol,” with the main function of reverse cholesterol transport (RCT) and negative correlation with atherosclerosis [8], little is known about alterations of metabolism, especially HDL, and how these multi-level variations affect aggressive diseases and poor outcomes. Patients with hepatitis B or hepatitis C have been shown to have possible lipid disorders, including decreased plasma HDL [5, 9]. However, whether HDL levels are correlated with HCC prognosis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the apparent phenotypic association with the polymorphism at aa 70, we were unable to detect any significant differences in comparisons of the polymorphism at aa 91. Although significant differences have been found in clinical observations between patients with the polymorphism at aa 91 in several reports, other reports have been contradictory 7 9 12 13 14 16 17 .…”
Section: Discussionmentioning
confidence: 92%
“…Akuta et al first reported that amino acid (aa) polymorphisms (Arg/Gln at aa 70 and Leu/Met at aa 91) in the core of the genotype 1b strain were potent predictors of poor response to IFN-based therapy 6 . Subsequently, several studies revealed that the polymorphism at aa 70 is more potent than the polymorphism at aa 91 and is associated with disease progression and development of hepatocellular carcinoma 7 8 9 10 11 12 13 14 15 16 17 18 . Notably, this is the only polymorphism in the HCV genome that is associated with both IFN treatment failure and the establishment of hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…Among patients infected with genotype-1b, those infected with a virus harboring amino acid substitutions at position 70 and/or 91 in the core protein have an elevated HCC risk 8 . The close association between amino acid 70 substitutions and increased HCC risk has been observed in several independent patient cohorts, but primarily in Asian (Japanese) populations 9 10 11 12 13 14 15 16 . Most notably, the increased HCC risk associated with amino acid 70 substitutions persists even after successful eradication of the virus with antiviral therapy 17 .…”
mentioning
confidence: 79%